The correlation between the increase rate of serum creatinine levels and long-term adverse clinical outcomes in patients with non st-segment elevation myocardial infarction - Arslan, Sukru; Mesut Dogan, Sait (Annals of Medical Research, 2021)
Aim: We purposed to evaluate the correlation between the rate of increase in SCrea levels and major adverse cardiac and cerebrovascular events(MACCE) in non ST-segment elevation myocardial infarction(NSTEMI) patients who was made coronary angiography(CAG) in this study. According to studies on especially stable coronary artery disease (SCAD); contrast-induced acute kidney injury CI-AKI) is described as an rising in serum creatinine (SCrea) levels more than 0.5 mg / dl or more than 25% within 48-72 hours after the contrast agent implementation. However, data on the increase rates of SCrea levels in patients with acute coronary syndrome (ACS) are insufficient..Materials and Methods: 884 NSTEMI patients were admitted to our study. We classified the patients into 3 groups according to the increase rates in SCrea values; first group(∆SCrea 10%), second group(10%≤ ∆SCrea 25%) and third group(∆SCrea ≥25%). Results: MACCE were defined as all-cause mortality, myocardial infarction (MI) and cerebrovascular accident (CVA) at one year follow-up. MACCE occurred in 123(13.9%) of the 884 patients. Patients in group three had a meaningfully higher rate of MACCE than in the other groups (P 0.001). This difference was primarily sourced from all-causes mortality; the all-causes mortality ratio was 3-4 times higher than the other groups. There was no meaningful difference in MACCE among first and second groups.Conclusion: Using an increase rate of ≥25% creatinine as the definition for CI-AKI is more reliable for primary end points in patients with NSTEMI than the increase rate of creatine in lower levels.
Keywords: Contrast induced nephropathy; serum creatinine increase ratio; acute coronary syndrome; adverse clinical outcomes